Implementation Of Learning Concept Of R.A.N.I Model On Mastery Of Mathematics Material At Sdn 04 Koto Ranah Lesson 2015/2016 - Masrida Masrida (Fakultas Sastra Universitas Ekasakti, 2018)
Primary school age around 6-12 years according to Mulyani Sumantri (Teaching and Learning Strategy 2001: 10) is an important and even fundamental development stage for the success of further development. Involvement in group life (collaboration or cooperation) for elementary school age children is of interest and concern. The development of emotional social relationships and the presence of normative ethical awareness in children of this age is a strong feature of elementary school age. Positive and productive social competencies will develop at this age such as the ability to work together, competence, tolerance, kinship and so on. In connection with the above, in the creation of a child learning environment is a development that provides opportunities for children to work in groups is very important. Giving children the opportunity to ask questions and do the questions in front of the classroom with teacher direction is a practical implication of the social-emotional and moral development of primary school-aged children. From the problems above, in the research can be formulated a formula of the problem as follows: Is the existence of the